Probabilistic analysis of the telegrapher's process with drift by means of relativistic transformations. (2001) - Beghin, L.; Nieddu, L.; Orsingher, E.
Abstract : The telegrapher's process with drift is here examined and its distribution is obtained by applying the Lorentz transformation. The related characteristic function as well as the distribution are also derived by solving an initial value problem for the generalized telegraph equation.